Chirality inversion in hydrogen-bonded rhodanine–oligothiophene derivatives by solvent and temperature. Issue 4 (15th December 2021) - Garcia, Ana M.; Ruiz-Carretero, Amparo
Abstract : Inversion of supramolecular chirality with a single enantiomer of a hydrogen-bonded pi-conjugated system is achieved by applying external stimuli such as solvent and temperature. Abstract : The self-assembly process of hydrogen-bonded quinquethiophene– rhodanine derivatives has been explored as a function of solvent and temperature. We demonstrate the divergent supramolecular chirality emerging from a single enantiomer by subtle changes in solvent mixtures and sample preparation protocol. Spectroscopic techniques have proved the presence of aggregates where H-bonding interactions play a crucial role.